Design of homogenous CNG-H and air mixer for diesel engines using particle swarm optimisation - Mahmood, Hussein Adel (2018)
A mixer is a device for mixing the proper amount of fuel with air before admission to the combustion chamber. Although an air–fuel mixer easily converts a diesel engine into a dual-fuel engine, and a petrol engine to a bi engine, the problem with gaseous mixers is the inability to prepare a homogeneous mixture of air and gaseous fuel at various engine speeds, and weak performance in controlling the AFR (air-fuel ratio) at various engine speeds. According to previous studies, no mixer has yet been designed for mixing H-CNG-air for tri-fuel engines (H-CNGDiesel engines). Moreover, the existing available mixers were unable to work under different engine modes (such as dual fuel or bi engine), different capacities of engine, or different mix of gaseous fuels. In this present work, a new air–HCNG mixer was designed and developed to be suitable for mixing air with (Hydrogen), (CNG) and (HCNG) under different modes (bi-engine, dual fuel engine, tri-fuel engine). In addition, this new mixer will allow super homogeneous mixing for gaseous fuels with air according to different engine speeds. The new mixer has been designed such that the mixer can be easily connected with an Electronic Control Unit (ECU) for accurate control of the air–gaseous fuel ratio for different engine speeds. The methodology includes theoretical analysis, numerical analysis and experimental work to validate the results of the numerical study. In the numerical part, 14 models of mixers with 116 cases were computer simulated to investigate the effects on the homogeneity and distribution of the mixture according to diameter size, location, and number of holes. The performance of the new mixer models was studied using (ANSYS FLUENT) with different air–gas fuel ratios (six cases), using a fully open valve, and with an engine speed of 4000 rpm. The results of the simulation indicated that the lowest UI (uniformity index) values compared with other models were obtained for a gaseous fuel range between 0.651 and 0.5107 using the different gaseous fuels with the existing mixer. By contrast, the highest UI values range between 0.954 and 0.939, and were obtained using the different gaseous fuels with model 6/case 47. The simulation results show that the new mixer exhibits superior performance in terms of achieving a homogenous mixture (CNG–air, H-air, and HCNG–air) at various engine speeds; the UI values range between 0.9336 and 0.967 under different AFRCNG, (0.941 to 0.974) under different AFRH, and (0.935 to 0.971) under AFRHCNG. Moreover, the new mixer shows a high level of accuracy in controlling the AFR according to the engine speed. In the practical investigation, the new air–fuel mixer (model 6, case 47) was fabricated based on the numerical analysis, and also on the new design for the movable mechanism, which consists of a small bevel gear, a large bevel gear, a power screw, a valve, bolts and seals. According to the numerical and practical results for the new mixer under different engine speeds (1000–4000), and an air–CNG ratio of 34.15, a meaningful agreement is reached between the experimental and numerical values for AFRCNG (R2 = 0.96 and CoV = 0.001494). In the theoretical part, two empirical models were proposed to estimate the UI of the gaseous fuel inside the new mixer models, and the valve displacements inside the new mixer model (model 6, case 47) based on the PSO technique. The results of the empirical models demonstrate the power of the PSO technique to solve the problem of heterogeneous mixtures inside the mixer, and to control the AFR inside the mixer, thereby enhancing the engine performance.